TRANSFORMASI WAKAF PRODUKTIF BERBASIS NILAI-NILAI AL-QUR'AN: PENDEKATAN STUDI KASUS DI INDONESIA - Munir, Misbahul (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
Productive waqf is a strategic instrument in Islamic economics with significant potential to address socio-economic challenges, such as income inequality and poverty, while simultaneously fostering sustainable development. This article explores the transformation of productive waqf based on the values of the Qur'an, employing a case study approach in Indonesia. Qur'anic principles, such as justice (QS. Al-Hadid: 18), sustainability (QS. Al-Baqarah: 267), and wealth redistribution (QS. Ali Imran: 92), serve as the primary foundation for the modern and productive management of waqf. Through literature analysis and case studies of institutions like the Indonesian Waqf Board (Badan Wakaf Indonesia/BWI) and Sinergi Foundation, this study identifies that integrating Qur'anic values with digital innovation and professional nazhir management enhances the effectiveness of waqf as a socio-economic instrument. The findings reveal that digitalization, sharia-based asset management, and community participation can overcome traditional challenges, such as low waqf literacy and limited nazhir capacity. Strategic recommendations are proposed to strengthen the synergy between the government, waqf management institutions, and the community, particularly in optimizing productive waqf assets to support economic empowerment and equitable redistribution of welfare.